2003
DOI: 10.1002/hed.10274
|View full text |Cite
|
Sign up to set email alerts
|

P53 mutation correlates with cisplatin sensitivity in head and neck squamous cell carcinoma lines

Abstract: These in vitro data support a role for mutation of the p53 tumor suppressor gene as a marker for response to cisplatin in HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
101
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 27 publications
(29 reference statements)
11
101
1
1
Order By: Relevance
“…The prognostic role of p53 in head and neck cancers is controversial [28]. Some authors found negative correlation between p53 expression and prognosis [29], while others including this study could not prove this finding [30,31].…”
Section: Discussionmentioning
confidence: 54%
“…The prognostic role of p53 in head and neck cancers is controversial [28]. Some authors found negative correlation between p53 expression and prognosis [29], while others including this study could not prove this finding [30,31].…”
Section: Discussionmentioning
confidence: 54%
“…The eight human HNSCC cell lines were chosen for this study because they (a) all express high level of EGFR, (b) have a wide range of sensitivity to the commonly used chemotherapy agent cisplatin, and (c) have known p53 and retinoblastoma status (25). 3 The cell lines were treated with retinoblastoma, which results in decreased retinoblastoma activity (27).…”
Section: Resultsmentioning
confidence: 99%
“…Carey (University of Michigan, Ann Arbor, MI). These cell lines have been extensively characterized and exhibit alterations detected in the majority of HNSCC, including epidermal growth factor receptor activation (26), constitutive activation of NF-nB and target genes (10 -12) and either wild-type (UMSCC-1, UMSCC-6, UMSCC-9, and UMSCC-11A) or mutant (UMSCC-11B and UMSCC-38) p53 genotype (27). 3 UMSCC-11A and UMSCC-11B were used for molecular studies because they have been shown previously to form xenografts and differ in sensitivity to chemotherapy agents, with UMSCC-11A being relatively more resistant to bortezomib and other agents in vitro and in mice in vivo (16).…”
Section: Inhibitors and Antibodiesmentioning
confidence: 99%